Old Norse Poetry and New Beginnings in Late 18th- and Early 19th- Century Literature - Gunnlaugsson, Gylfi (Presses de l'Université du Québec, 2011)
This article first examines the image of northern antiquity conveyed in the productive reception of Old Norse literature by European writers and poets in the later 18th century, when this heritage at last attracted a non-scholarly international readership. Initially, European writers were impressed especially by the primitive and the sublime in Old Norse literature. This is partly attributable to the unusual character of the small selection of Old Norse poetry that had been translated into Latin. Secondly, the reception was informed by growing dissent against classicism in the European literary world and the consequent search for alternatives. The main part of the article then considers whether a similar emphasis may be discerned in Icelanders’ reception of Old Norse literature a little later. The focus is on the resurrection of eddic metres, at first most evident in scholarly writings and in translations of lengthy epic poems, and later manifested in original poetry by Bjarni Thorarensen and other poets. Further aspects of Thorarensen’s creative reception of Old Norse literature are also examined in light of the reception in other countries; and his ideas about the North in a broad sense, and Iceland’s place in it, are discussed. Subsequently Thorarensen’s views on Iceland’s status within the kingdom of Denmark are analyzed. Finally the point is elaborated that Thorarensen approaches Old Norse literature primarily as the common heritage of a supranational North.